Roles of working memory, syllogistic inferencing ability, and linguistic knowledge on second language listening comprehension for passages of different lengths. (October 2022) - Kim, Minkyung; Nam, Yunjung; Crossley, Scott A.
This study investigated the effects of working memory capacity (WMC), first language (L1) syllogistic inferencing ability, and second-language (L2) linguistic knowledge on L2 listening comprehension for passages of different lengths. Participants were 193 Korean ninth-grade learners of English. A path analysis was used to examine multivariate relationships among variables. Findings indicated that L2 linguistic knowledge was pivotal in explaining L2 listening comprehension for passages of different lengths. Findings also indicated that over and above L2 linguistic knowledge, greater WMC facilitated comprehending longer L2 listening passages, while better L1 syllogistic inferencing ability facilitated comprehending shorter L2 listening passages. WMC may help form more information-dense representations of longer passages, while L1 syllogistic inferencing ability may help build integrated propositional representations of shorter passages. In addition, greater WMC had indirect impacts on L2 listening comprehension through L1 syllogistic inferencing ability and L2 linguistic knowledge, which suggests that WMC may lead to better L2 listening comprehension when learners have greater L2 knowledge or better L1 syllogistic inferencing ability. Overall, first, this study suggests a pivotal role for L2 linguistic knowledge in L2 listening comprehension and, second, roles for WMC and L1 syllogistic inferencing, which function differently depending on passage length.